Antimicrobial resistance of Salmonella strains isolated from food products of animal origin in Ukraine between 2018-2021 - Tamara Kozytska; Olha Chechet; Tetiana Garkavenko; Vitalii Nedosekov; Olha Haidei; Olga Gorbatiuk; Valentyna Andriyashchuk; Viacheslav Kovalenko; Diana Ordynska; Natalia Kyriata (German Journal of Veterinary Research)
Salmonellosis is a zoonotic infection of humans and animals. In recent years, an increase in the number of resistant strains of Salmonella from animals and animal products have been recorded. We conducted microbiological testing and antibiotic resistance profile of 34 Salmonella strains isolated from foods of animal origin between 2018 to 2021 in Ukraine. Twenty isolates were successfully assigned to six different serovars [S. Enteritidis (n=13, S. Infantis (n=2), S. Schwarzengrund (n=1), S. Livingstone (n=2), S. Vuadens (n=1) and S. Hadar (n=1)], and 14 isolates remained untyped. Most of the isolated strains were recovered from poultry products. The strains were tested for six antibacterial groups: quinolones, aminoglycosides, β-lactams, cephalosporins, phenols, and dihydrofolate reductase inhibitors by disc diffusion method. The highest level of resistance was recorded to 4th generation cephalosporins, e.g., cefepime (88.2%). The lowest level of resistance was to cefotaxime and ceftriaxone (5.9%). No resistance was found to imipenem and aminoglycoside antibiotics, particularly gentamicin and amikacin. The study results are of concern because antibiotic-resistant bacteria and their genes can cause human infections by penetration and transmission at any stage of the food production cycle. Further research is required to monitor the contamination of food products of animal origin with salmonellosis pathogens, including antibiotic-resistant strains